Design of electronic method for assessment of is services quality - Alias, Rose Alinda (2001)
This paper is divided into three major parts. The first part begins by introducing traditional and current methods of survey and assessment. Traditional methods of assessment include phone survey, mail survey, and face-to-face survey. Survey research accounted for 36.3% of research publications by leading institutions in US (Falconer and Hodgett, 1999). With the advent of Internet and the World Wide Web, assessment has gone online. Latest tools and technologies have been utilized to improve accessibility and introduce flexibility to the respondents. Regardless of the method, a set of questions is put forward to the intended respondent. The respondent will provide answers in the form of views, perceptions, or opinions. The response rates obtained from these methods are least encouraging. Researchers have given various reasons for the low response rate and have suggested possible remedies to improve response rates as reported in Falconer and Hodgett, (1999), Ballantyne, (2000). The second part of the paper is concerned on IS services. IS services are defined as activities that facilitate and support customers in exploiting IS in organization. The various types of IS services can be categorized into three major groups: development service, use service and user support service (Saaksjarvi and Saarinen, 1994). The SERVQUAL instrument is adapted from Parasuraman et. al. (1985) as the content of the questionnaire. The final part proposes a design of online assessment method that takes into account the various stakeholders (respondents, owners, and administrators) views. The proposed online method is examined through the system design, which deals with how the method is developed. This paper shows that the online assessment method is actually part of a larger â€œinformation systemâ€ which is governed by the interaction among the stakeholders, the processes, environment, and other external factors.